T‐cell acute lymphoblastic leukemia in infants has distinct genetic and epigenetic features compared to childhood cases. Issue 2 (26th October 2016) - Doerrenberg, Mareike; Kloetgen, Andreas; Hezaveh, Kebria; Wössmann, Wilhelm; Bleckmann, Kirsten; Stanulla, Martin; Schrappe, Martin; McHardy, Alice C; Borkhardt, Arndt; Hoell, Jessica I
Abstract : For reasons not yet understood, nearly all infants with acute lymphoblastic leukemia (ALL) are diagnosed with the B‐cell type, with T‐ALL in infancy representing a very rare exception. Clinical and molecular knowledge about infant T‐ALL is still nearly completely lacking and it is also still unclear whether it represents a distinct disease compared to childhood T‐ALL. To address this, we performed exome sequencing of three infant cases, which enabled the detection of mutations in NOTCH2, NOTCH3, PTEN, and KRAS . When analyzing the transcriptomes and miRNomes of the three infant and an additional six childhood T‐ALL samples, we found 760 differentially expressed mRNAs and 58 differentially expressed miRNAs between these two cohorts. Correlation analysis for differentially expressed miRNA‐mRNA target pairs revealed 47 miRNA–mRNA pairs, with many of them previously described to be aberrantly expressed in leukemia and cancer. Pathway analysis revealed differentially expressed pathways and upstream regulators related to the immune system or cancerogenesis such as the ERK5 pathway, which was activated in infant T‐ALL. In summary, there are distinct molecular features in infant compared to childhood T‐ALL on a transcriptomic and epigenetic level, which potentially have an impact on the development and course of the disease. © 2016 Wiley Periodicals, Inc.